2018
DOI: 10.1136/jclinpath-2018-205485
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine lesions of the breast: part 2 of a two-part review. Invasive apocrine carcinoma, the molecular apocrine signature and utility of immunohistochemistry in the diagnosis of apocrine lesions of the breast

Abstract: Pure apocrine carcinoma of the breast is rare and has been defined by using a combination of morphologic (apocrine morphology in >90% of tumour cells) and immunohistochemical criteria (oestrogen receptor (ER) and progesterone receptor (PR) negative and androgen receptor (AR) positive). Recent advances in the molecular classification of breast tumours have uncovered a subset of breast tumours associated with high expression of androgen receptor mRNA including the so-called ‘luminal androgen receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…5b, Supplementary Fig. 11), consistent with the disconnect between AR expression and AR signaling in breast cancer noted by others 26 . Also, for patient BCN1371, we did not observe significant upregulation of PI3K signaling (Fig.…”
Section: Exploration Of Response Features In Individual Non-pcr Casessupporting
confidence: 88%
“…5b, Supplementary Fig. 11), consistent with the disconnect between AR expression and AR signaling in breast cancer noted by others 26 . Also, for patient BCN1371, we did not observe significant upregulation of PI3K signaling (Fig.…”
Section: Exploration Of Response Features In Individual Non-pcr Casessupporting
confidence: 88%
“…The five non-pCR cases were stained for the pan T-cell marker CD3 to validate these proteogenomic findings ( Figure 5D). Consistent with the active immune microenvironment ( Figure 5C Figure 5D) without activation of an androgen response signature or apocrine features ( Supplementary Figure 11), consistent, with the disconnect between AR expression and AR signaling in breast cancer noted by others 26 . Also, for patient BCN1371, we did not see significant upregulation of PI3K signaling ( Figure 5B) despite PIK3CA mutation (E545K), consistent, with the disconnects between PIK3CA mutation and effects when signaling was assessed by reverse phase protein array (RPPA) 19,27 .…”
Section: Proteomics and Phosphoproteomic Analyses Of Acute On-treatmesupporting
confidence: 87%
“…The apocrine subtype of triple-negative breast cancers is also recognized on the basis of gene-expression profiles. 11,12 The association between papillary lesions and apocrine changes represents a great challenge for breast pathologists. Papotti et al first reported areas of apocrine differentiation in papillary breast carcinomas with and without invasion.…”
Section: Discussionmentioning
confidence: 99%
“…9 Apocrine lesions, for many pathologists, imply an ER and PR negative status by definition. 10,11 Malignant apocrine tumors may be HER2 negative or positive, the tumor being triple-negative in the first setting. The apocrine subtype of triple-negative breast cancers is also recognized on the basis of gene-expression profiles.…”
Section: Discussionmentioning
confidence: 99%